An investigation of using palm biodiesel blend on the performance of a stationary marine diesel engine - C. W., Mohd Noor; R., Mamat; Wan Mohd, Norsani; M. M., Noor (Science & Technology Research Institute for Defence (STRIDE), 2016)
Most of marine vehicles use petroleum based fuel as the source of energy in their daily operations. However, volatile oil price and concerns over depletion of petroleum resources have hastened researchers to look for other alternative fuel. As a result, biodiesel has been identified as one of the environmentally friendly alternatives energies and at the same time can reduce our dependency on petroleum-based fuels. The present study investigates the effects of palm biodiesel blends on stationary marine diesel engines with regards to the engines’ performance characteristics, such as brake power, brake specific fuel consumption, exhaust gas temperature, brake thermal efficient and NOX emissions. The experiment was conducted using Cummins NT-855 marine diesel engines. The results revealed that the use of palm biodiesel blends increased the brake specific fuel consumption, NOX emissions and exhaust gas temperature up to 18.75%, 26.15% and 5.5% respectively. On the other hand, it contributed to reduced brake thermal efficiency by 12.17%. On one hand, palm biodiesel does not give any significant difference in engine brake power when compared to petroleum diesel. On the whole, it is proved that low blend palm biodiesel can be used in marine diesel engines, thereby providing a viable alternative to petroleum diesel.